Impact of Operational Condition on the Membrane Permeate Flux and Quality of Domestic Wastewater Treatment using Hollow Fiber Membrane Module in Cross-Flow Mode - Khan Bushra; Liu Mei; Natsagdorj Khaliunaa; Rooha Khurram; Zhan Wang (Journal of Chemical Engineering Research Updates, 2018)
In this paper, the impacts of process conditions on the membrane permeate flux (J) and the quality of effluent in domestic wastewater treated by using 0.1 μm hollow fiber membrane module in cross-flow mode were quantificationally analyzed with a statistical method. The results showed that (1) trans-membrane pressure (TMP), crossflow velocity (u), mixed liquor suspended solids (MLSS), dissolved oxygen concentration (DO), pH, temperature (T), sludge retention time (SRT) and hydraulic retention time (HRT) were all the influencing factors of the permeate flux. Among them, MLSS, T, SRT and HRT are negative contributors to the permeate flux while TMP, u, DO and pH are positive contributors. In addition, the quantitative relationship between the permeate flux and process conditions is established. (2) TMP and u had no effect on the quality of effluent COD while other operating conditions were the influencing factors. Only HRT had a negative effect on the quality of effluent NH3-N. The quantitative relationships between COD, TOC, NH3-N and process conditions were also established. These mathematical expressions, to some extent, could be used to optimize operational conditions, predict the permeate flux and efficiency of domestic wastewater treatment using hollow fiber membrane module in cross flow mode.